Diverse contribution of Col2a1‐expressing cells to the craniofacial skeletal cell lineages. (June 2017) - Sakagami, N.; Ono, W.; Ono, N.
Structured Abstract: Objectives: Craniofacial skeletal development requires deliberate coordination of two distinct mechanisms of endochondral and intramembranous ossification. Col2a1‐ expressing cells encompass growth‐associated skeletal progenitors in endochondral bones of the limb. The objective of this study was to determine the contribution of Col2a1 ‐expressing cells to the craniofacial skeletal cell lineages. We hypothesize that Col2a1‐ expressing progenitors significantly contribute to various modes of ossification associated with the craniofacial development. Methods: Cellular fates of Col2a1 ‐expressing cells were studied based on a cre‐loxP system using a Col2a1‐cre transgene and an R26R‐ tdTomato reporter allele. We analysed three distinct locations of the craniofacial skeletal complex representing unique ossification mechanisms: the cranial base, the calvaria and the mandibular condyle. Results: Col2a1‐cre consistently marked a majority of skeletal cells in the cranial base. Interestingly, Col2a1‐cre also marked a large number of osteoblasts and suture mesenchymal cells in the calvaria, in addition to chondrocytes in the underlying transient cartilage. In the mandibular condyle, Col2a1‐cre marked chondrocytes and osteoblasts only during the growth phase. Conclusions: Col2a1 is expressed by progenitors of the skeletal lineage in canonical endochondral bone formation occurring in the cranial base. In contrast, other ossification mechanisms of the craniofacial complex utilize Col2a1‐ expressing cells in a different manner, whereby Col2a1 may be expressed in more differentiated or transient cell types of the skeletal lineage.